Highly Improved Copper-Mediated Michael Addition of Ethyl Bromodifluoroacetate in the Presence of Protic Additive - Kim, Bong Chan; Park, Aeri; An, Ji Eun; Lee, Won Koo; Lee, Hee Bong; Shin, Hyunik (Synthesis, 2012)
Copper-mediated Michael addition of ethyl bromodifluoroacetate to Michael acceptors is accompanied by the formation of a substantial amount of byproducts. Elucidation of their structure hinted the cause of their formation, from which we discovered a highly improved and robust protocol by treatment with protic additives such as H2O and AcOH. This modification led to significant increase of yield with concomitant decreased use of reagent.
Keywords: copper; coupling; fluorine; Michael addition; protonation